Faktor Penghambat Penanganan Komentar Netizen Yang Mengandung Kebencian Hate Comments Netizen di Tinjau dari Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik (Study Kasus Pada Kepolisian Resort Kupang Kota) - lega, maria yosefa elista; Medan, Karolus Kopong; Manafe, Deddy R. CH. (Law Faculty, Nusa Cendana University, 2024)
Malicious comments from netizens circulating on social media in Kupang City are increasingly frequent. Over the past five years, there have been 225 police reports regarding malicious comments from netizens whose content leads to criminal acts of insult and/or defamation and hate speech, but the handling by the police in the Kupang City Police Resort area has not been optimal. Therefore, the main problem of this study is what are the inhibiting factors in handling malicious comments from netizens and the efforts made by the police in the Kupang City Police Resort area to overcome these inhibiting factors. The purpose of this study is to determine and describe the inhibiting factors and efforts made by the police in the Kupang City Police Resort area in handling malicious comments from netizens in Kupang City. The methods used are document/literature studies and field research by interviewing a number of key informants. The findings of this study show that the inhibiting factors in handling malicious comments from netizens by the police in the Kupang City Police Resort are (1) limited number, quality and capability of police personnel who are authorized and tasked with handling cybercrime, including malicious comments from netizens; (2) limited supporting facilities and infrastructure, both quantitatively and qualitatively, such as equipment and finances; (3) lack of knowledge and understanding of laws and regulations regarding netizen hate comments.